Detection and Inhibition of Bacteria on a Dual‐Functional Silver Platform. Issue 3 (25th October 2018) - Vedarethinam, Vadanasundari; Huang, Lin; Xu, Wei; Zhang, Ru; Gurav, Deepanjali D.; Sun, Xuming; Yang, Jing; Chen, Ruoping; Qian, Kun
Abstract: Detection and inhibition of bacteria are universally required in clinics and daily life for health care. Developing a dual‐functional material is challenging and in demand, engaging advanced applications for both defined bioanalysis and targeted biotoxicity. Herein, magnetic silver nanoshells are designed as a multifunctional platform for the detection and inhibition of bacteria. The optimized magnetic silver nanoshells enable direct laser desorption/ionization mass spectrometry based metabolic analysis of bacteria (≈10 µL −1 ), in complex biofluids. The serum infection process (0–10 h) is monitored by statistics toward clinical classification. Moreover, magnetic silver nanoshells facilitate surface adhesion on bacteria due to nanoscale surface roughness and thus display long‐term antibacterial effects. Bacteria metabolism is studied with metabolic biomarkers (e.g., malate and lysine) identified during inhibition, showing cell membrane destruction and dysfunctional protein synthesis mechanisms. This work not only guides the design of material‐based approaches for bioanalysis and biotoxicity, but contributes to bacteria‐related diagnosis by using specific metabolic biomarkers for sensitive detection and new insights by monitoring metabolomic change of bacteria for antibacterial applications. Abstract : A dual‐functional silver platform is constructed for the detection and inhibition of bacteria, toward real case applications and biological understanding. The designed platform achieves defined bioanalysis and targeted biotoxicity.